Impact of the Peace Agreement on the social determinants of health in Colombia - Edna Johana Mondragón-Sánchez; Reinaldo Gutiérrez Barreiro; Marcos Venícios de Oliveira Lopes; Ana Karina Bezerra Pinheiro; Priscila de Souza Aquino; Patrícia Neyva da Costa Pinheiro
ABSTRACT Objectives: to analyze the impact of the Colombian Peace Agreement on the structural social determinants of health. Methods: a descriptive, ecological study, based on documentary data from 2008 to 2018. The records of victims, epidemiological indicators, and structural social determinants of health in Colombia were analyzed. Results: there was a correlation between the period in which the Peace Agreement process was developed and the indicators of structural determinants in health with p<0.05. With the Poisson regression analysis, the favorable correlations between the peace process and the determinants were confirmed, besides allowing the understanding of the changes in these indicators before the Peace Agreement. Conclusions: the implementation of the peace process has a positive impact on structural social determinants of health, which is observed by the beginning of the decrease of economic, educational, health, and social inequalities and inequities, a fact that offers the possibility of living in peace.